Global Longitudinal Strain and Myocardial Work Index in Post-COVID-19 Syndrome with Mild Symptoms: A Case Series - Prima Almazini; Amiliana Mardiani Soesanto (Acta Medica Indonesiana, 2023)
The involvement of the cardiovascular system in COVID-19 is prevalent. The effect of SARS-COV-2 infection in both acute and recovery phases is called a post-COVID-19 syndrome. Considering the high prevalence of cardiac abnormalities after COVID-19, clinicians should continue to monitor cardiac function in COVID-19 patients after hospital discharge. Echocardiography is an accurate and accessible tool to assess cardiac function after COVID-19. Left-ventricle (LV) and right ventricle (RV) longitudinal strains are more sensitive to detecting subtle abnormalities than standard parameters, such as left-ventricle ejection fraction and tricuspid annular plane systolic excursion (TAPSE). Myocardial work index is a novel parameter including afterload to evaluate cardiac function. These parameters can give further information on cardiac function in COVID-19 patients. We presented two cases of COVID-19 with serial cardiac assessment using echocardiography.